Subscription economy in the leisure behavior of Polish consumers - Ziobrowska-Sztuczka, Justyna; Markiewicz, Ewa (Bulletin of Geography. Socio-economic Series, 2025)
The article aims to determine the preferences of Polish consumers in the use of the subscription model in their leisure time behaviors, taking into account the size of their place of residence. The study employed a diagnostic survey method and statistical analysis as the research approach. The authors' research has shown great interest in the subscription model among Polish respondents in behaviors related to spending leisure time; however, no significant differences were observed between the studied groups based on place of residence, indicating a consistent pattern of consumer preferences among respondents from both urban and rural environments. The main areas of interest turned out to be primarily VoD platforms and music streaming, and the most important factor influencing consumer behavior in the context of subscription services is the economic factor, mainly the price of the subscription...n.